THE CORRELATION BETWEEN THE HISTORY OF HYPERTENSION AND PREECLAMPSIA - Sukmawati .; Lilis Mamuroh; Furkon Nurhakim (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
The maternal mortality rate in Garut Regency was 74 cases in 2016 and 25% of them was due to preeclampsia. There were 96 pregnant women treated for Preeclampsia from January to November 2017 in the Kalimaya Room of Dr. Slamet Garut Hospital. Preeclampsia is an increase in blood pressure in pregnant women after 20 weeks of pregnancy and proteinuria. The purpose of this study was to determine the relationship between the history of hypertension and the incidence of preeclampsia in the Kalimaya Room of Dr. Slamet Garut Hospital. This research applied the analytic correlation method with Case-Control approach. Simple Random Sampling was chosen, and the number of samples was 49 respondents as the case group and the control group was 98 respondents. Data were analyzed using univariate, bivariate analysis with Chi-Square test. The results showed a relationship between the history of hypertension (p=0.0001) and the incidence of preeclampsia. The results of this study are expected to be a reference for families to get to know as early as possible the risk factors for preeclampsia, especially a history of hypertension. Health workers can provide counseling to pregnant women about interventions to prevent preeclampsia and its treatment.Keywords: hypertension, preeclampsia, pregnancy